Intellectual Capital and Managerial Ownership at the Cost of Capital: Earnings Management as Moderation: Modal Intelektual Dan Kepemilikan Manajerial Pada Biaya Modal: Manajemen Laba Sebagai Moderasi - Supriadi, Adi; Aryati, Titik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine and analyze empirically the effect of managerial ownership and intellectual capital on the cost of capital moderated by earnings management. The population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the sample is determined by purposive sampling. The sample used consisted of 73 companies during the 2016-2019 period. All variables are measured by their respective ratios, earnings management is measured by Stubben's discretionary income model, this research hypothesis is tested using multiple regression using eviews 9 as an analysis tool. The results of the first hypothesis show that managerial ownership has no significant effect on capital either positively or negatively. The results of the second hypothesis that intellectual capital has a negative effect on the cost of capital have been proven because in addition to being significant in this study, it is also in accordance with the hypothesis that the researcher made. The results of the third hypothesis of earnings management strengthen the effect of managerial ownership on the cost of capital, it is not proven because earnings management as a moderating variable in the study has no effect. The results of the fourth hypothesis that earnings management weaken the influence of intellectual capital on the cost of capital are not proven because earnings management in this study as a moderating variable in this study has no effect.